Cạnh tranh và ổn định ngân hàng – Vai trò điều tiết của bất định chính sách kinh tế - Lê Huỳnh, Như; Võ Xuân, Vinh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study examines the moderating role of economic policy uncertainty (EPU) the relationship between competition and bank stability in 20 countries over the period 2009 to 2023. Using an instrumental variable (IV) approach through the generalized method of moments (GMM), based on unbalanced panel data at the bank level, the results support the competition-stability hypothesis and confirm the moderating effect of economic policy uncertainty on the relationship between bank competition and bank stability via the economic policy uncertainty index. This is firmly supported by feasible generalized least squares (FGLS) estimation, robust ordinary least squares (Robust OLS) estimation, and Driscoll-Kraay standard error regression. However, all of them do not find similar results with economic policy uncertainty measured through the world uncertainty index (WUI). The empirical findings provide specific policy implications for bank managers and policymakers in making decisions to enhance competitiveness and stabilize the banking system amid current economic policy uncertainty.
Keywords: Banking stability; Banking competition; Economics policy uncertainty